Lord of the shadows / 11. - Shan, Darren (The Saga of Darren Shan, 2007)
When Darren Shan returns home, he is met by old enemies and scores to be settled, and with destiny certain to destroy him, the world seems doomed to fall to the Ruler of the Night.